Analisis Pemahaman Hukum Islam Melalui Metode Mantuq Dan Mafhum Dalam Menyelesaikan Permasalahan Ibadah Dan Muamalah - Fredela nesyah; Indah Tuti Agustin; Gustiya Sunarti (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
The analysis of Islamic legal understanding through the methods of mantuq and mafhum plays a significant role in addressing issues related to both worship (ibadah) and social transactions (muamalah). The mantuq method refers to the derivation of rulings based on the explicit meaning of Qur’anic and Hadith texts, while the mafhum method is employed to extract rulings through the implicit meanings embedded within the scriptural language. Both methods serve as essential argumentative foundations for scholars and practitioners of Islamic law in responding to the dynamic challenges faced by Muslim communities. In the sphere of worship, these methods provide clarity on matters such as differences in prayer practices or the determination of prayer times. In the realm of muamalah, their relevance is evident in contemporary issues including digital transactions, electronic money, and technology-based zakat management. This study adopts a qualitative approach through library research, examining both classical and modern literature in the fields of usul al-fiqh, Qur’anic exegesis, and Hadith, while also comparing classical scholarly opinions with contemporary fatwas, such as those issued by the National Sharia Council of Indonesia (DSN-MUI). The findings are expected to enrich the methodological discourse of istinbath al-ahkam (derivation of legal rulings), reaffirm the relevance of mantuq and mafhum, and provide practical solutions to current issues in worship and social transactions..